Cell Membrane-Based Biomimetic Nanoparticles and the Immune System: Immunomodulatory Interactions to Therapeutic Applications - Sushnitha, Manuela; Evangelopoulos, Michael; Tasciotti, Ennio; Taraballi, Francesca (Frontiers in Bioengineering and Biotechnology, 2020)
Nanoparticle-based drug delivery systems have been synthesized from a wide array of materials. The therapeutic success of these platforms hinges upon their ability to favorably interact with the biological environment (both systemically and locally) and recognize the diseased target tissue. The immune system, composed of a highly coordinated organization of cells trained to recognize foreign bodies, represents a key mediator of these interactions. Although components of this system may act as a barrier to nanoparticle delivery, the immune system can also be exploited to target and trigger signaling cues that facilitate the therapeutic response stemming from systemic administration of nanoparticles. The nano-bio interface represents the key facilitator of this communication exchange, where the surface properties of nanoparticles govern their in vivo fate. Biomimetic nanoparticles have emerged as one approach to achieve targeted drug delivery by actively engaging and communicating with the biological milieu. In this review, we will highlight the relationship between biomimetic nanoparticles and the immune system, emphasizing the role of tuning the nano-bio interface in the immunomodulation of diseases. We will also discuss the therapeutic applications of this approach with biomimetic nanoparticles, focusing on specific diseases ranging from cancer to infectious diseases. Lastly, we will provide a critical evaluation on the current state of this field of biomimetic nanoparticles and its future directions in immune-based therapy.